Exploring the effect of type 2 diabetes on brain structure and cerebral perfusion in patients with early Alzheimer's disease: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Dake, Manmohi D; De Marco, Matteo; Wilkinson, Iain; Teh, Kevin; Mitolo, Micaela; Remes, Anne; Liu, Yawu; Pikkarainen, Maria; Soininen, Hilkka; Venneri, Annalena
Abstract: Background: Past research has shown that Alzheimer's Disease (AD) can have a significant detrimental effect on the cerebrovascular system. Previous work has also indicated that type 2 diabetes mellitus (T2DM), along with being a risk factor for AD, shares certain similarities with AD in terms of the mechanisms affecting the cerebrovascular system. Hence, comorbid T2DM in AD could cause additional cardiovascular burden that may cause further damage to brain structure and function than that seen in AD. Method: The current study compares 54 patients across the AD spectrum with and without T2DM (with 27 patients in each group). Voxel based morphometry was used to determine volumetric differences in grey matter using T1‐weighted magnetic resonance images. To assess whether these volumetric differences were associated with a reduction in cerebral blood flow, arterial spin labelling (ASL) was used to measure cerebral perfusion. Results: Patients with T2DM had smaller grey matter volume compared to patients without T2DM in the anterior caudate nucleus and posterior cerebellum in the right hemisphere. Perfusion deficits mirrored the regional volumetric abnormalities, along with additional hypoperfusion observed in the right parahippocampal gyrus. These differences were also associated with deficits in cognitive function. Conclusions: Microvascular and macrovascular complications seen in the AD patients with comorbid T2DM could therefore contribute toward the negative effects exerted on cerebral perfusion that could potentially contribute toward the structural deficits observed. Furthermore, the right lateralised effects seen in the present study could arise due to the characteristic trajectory of the arteries supplying the brain. With the increasing prevalence of cardiovascular risk factors such as T2DM combined with the rise in numbers of people living with AD, the additional cardiovascular burden caused by such risk factors may be a crucial tipping point toward conversion to AD dementia from prodromal stages. This is one of the first studies to show that the additional cerebrovascular burden resulting from comorbid T2DM in AD can result in worse structural and perfusion deficits using multi‐modal neuroimaging and that these deficits can be associated with clinical presentations.